CAR products from novel sources: a new avenue for the breakthrough in cancer immunotherapy - Huang, Jiawen; Yang, Qian; Wang, Wen; Huang, Juan (Frontiers in Immunology, 2024)
Chimeric antigen receptor (CAR) T cell therapy has transformed cancer immunotherapy. However, significant challenges limit its application beyond B cell-driven malignancies, including limited clinical efficacy, high toxicity, and complex autologous cell product manufacturing. Despite efforts to improve CAR T cell therapy outcomes, there is a growing interest in utilizing alternative immune cells to develop CAR cells. These immune cells offer several advantages, such as major histocompatibility complex (MHC)-independent function, tumor microenvironment (TME) modulation, and increased tissue infiltration capabilities. Currently, CAR products from various T cell subtypes, innate immune cells, hematopoietic progenitor cells, and even exosomes are being explored. These CAR products often show enhanced antitumor efficacy, diminished toxicity, and superior tumor penetration. With these benefits in mind, numerous clinical trials are underway to access the potential of these innovative CAR cells. This review aims to thoroughly examine the advantages, challenges, and existing insights on these new CAR products in cancer treatment.